PENGARUH RASIO KEUANGAN, SALES GROWTH, DAN KEBIJAKAN DIVIDEN TERHADAP PERUBAHAN HARGA SAHAM - Ansori, Achmad Fawaid; Riharjo, Ikhsan Budi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2022)
This research aimed to examine to examine and find out the effect of Finance, Sales Growth, and Dividen Policy on Stock Price Change. The Population was 36 manufacturing companies that were listed on Indonesia Stock Exchange (IDX) from 2017-up to 2020. Moreover, the research was quantitative. Furthermore, the data collection technique user purposive sampling. In line wiht that, there were 110 sample of manufacturing companies. Additionally, the data analysis technique used multiple linear regression. The research result concluded that Return On Asset (ROA) had a positive effect on stock price change, Return On Equity (ROE) had a positive effect on stock price change. On the other hand, the Current Ratio (CR) did not affect stock price change. In contast, Sales Growth had a positive effect on stock price change. On the contrary, the Dividend Payout Ratio did not affect the stock price change of manufacturing companies that were listed on the Indonesia Stock Exchange (IDX) from 2017-up to 2020.